Oblique half-graben inversion of the Mesozoic Neuquén Rift in the Malargüe Fold and Thrust Belt, Mendoza, Argentina: New insights from analogue models - Yagupsky, Daniel Leonardo (2008)
The Malargüe fold and thrust belt, located in the Andean mountains between 34°S and 36°30′S, formed in response to contraction during Cenozoic times. Its structural style and geometry was controlled by the Mesozoic rift system that formed the Neuquén basin in west-central Argentina. The rift architecture in the southern sector of this belt was previously interpreted in terms of the present N-S compressive structural trends, assuming the inversion of pre-existing normal faults with the same orientation. Here, we propose that the NW-SE-trending El Manzano-Liu Cullín lineament, located in the northern termination of the Sierra Azul, reflects the presence of a half-graben master fault in the subsurface. This hypothesis is supported by subsurface data, a balanced cross section, and it is tested using a series of scaled sandbox analogue models. We suggest that the lineament responds to a reactivated NW-trending half-graben fault, hidden by the mainly N-S-trending Andean structures. The proposed orientation is in agreement with the NE-SW extension developed in the Neuquén basin during the Triassic-Early Jurassic. The modeling of the inverted oblique half-graben reveals that the strikes of the main structures of inversion-related belts may often be independent of the orientation of the previously developed extensional system, providing a new perspective for their interpretation.